Spread-out Bragg peak FLASH: quantifying normal tissue toxicity in a murine model - Kristensen, Line; Poulsen, Per Rugaard; Kanouta, Eleni; Rohrer, Sky; Ankjærgaard, Christina; Andersen, Claus E.; Johansen, Jacob G.; Simeonov, Yuri; Weber, Uli; Grau, Cai; Sørensen, Brita Singers (Frontiers in Oncology, 2024)
Objective: A favourable effect of ultra-high dose rate (FLASH) radiation on normal tissue-sparing has been indicated in several preclinical studies. In these studies, the adverse effects of radiation damage were reduced without compromising tumour control. Most studies of proton FLASH investigate these effects within the entrance of a proton beam. However, the real advantage of proton therapy lies in the Spread-out Bragg Peak (SOBP), which allows for giving a high dose to a target with a limited dose to healthy tissue at the entrance of the beam. Therefore, a clinically relevant investigation of the FLASH effect would be of healthy tissues within a SOBP. Our study quantified the tissue-sparing effect of FLASH radiation on acute and late toxicity within an SOBP in a murine model.Material/Methods: Radiation-induced damage was assessed for acute and late toxicity in the same mice following irradiation with FLASH (Field dose rate of 60.0 Gy/s) or conventional (CONV, 0.34 Gy/s) dose rates.The right hindleg of unanaesthetised female CDF1 mice was irradiated with single-fraction doses between 19.9-49.7 Gy for CONV and 30.4-65.9 Gy for FLASH with 5-8 mice per dose. The leg was placed in the middle of a 5cm Spread-out Bragg Peak (SOBP) generated from a mono-energetic beam using a 2D range modulator. Acute skin toxicity quantified by hair loss, moist desquamation and toe separation was monitored daily within 29 days post-treatment. Late toxicity of fibrotic development measured by leg extendibility was monitored biweekly until 30 weeks post-treatment.Comparison of acute skin toxicity following radiation indicated a tissue-sparing effect of FLASH compared to conventional single-fraction radiation with a mean protection ratio of 1.40 (1.35-1.46). Fibrotic development similarly indicated normal tissue sparing with a 1.18 (1.17-1.18) protection ratio. The acute skin toxicity tissue sparing was similar to data from entrance-beam irradiations of Sørensen et al. (4).Full dose-response curves for acute and late toxicity after CONV and FLASH radiation were obtained. Radiation within the SOBP retains the normal-tissue-sparing effect of FLASH with a dosemodifying factor of 40% for acute skin damage and 18% for fibrotic development.